Feedback for coaches: Who coaches the coach? - Nash, C.; Sproule, J.; Horton, P. (International Journal of Sports Science & Coaching, 2017)
The aim of this study was to investigate the feedback mechanisms that sport coaches utilized to enhance their coaching practice at various stages of their careers. Sport coaches (n=21) were interviewed in-depth with the resulting information being analysed using HyperRESEARCH qualitative data analysis software package. Results suggested four distinct dimensions that characterized the sources of feedback used by coaches: networks, players/participants, critical thinking skills and support systems. Those more experienced coaches with established networks of like-minded coaches seemed to be more open to constructive feedback. Similarly, novice coaches appeared to accept feedback from non-reliable sources in lieu of more informed sources. A distinctive emerging feature was the lack of formal feedback mechanisms within groups of coaches at all levels of qualification.